Penentuan Harga Pokok Produksi Produk Ayam Geprek dengan Metode Full Costing - Angelica Permata Kurniawan; Wianda Gracia Sugiono; Diyana Diyana; Siti ‘Ainun Galbini; Atanasius Hagai Pratama; Ade Elza Surachman (Nusantara Mengabdi Kepada Negeri, 2024)
This service aims to improve the understanding and skills of MSME entrepreneurs in calculating production costs using the full costing method at the geprek chicken business located on Jl. Dr. Sudarsono No.34, Cirebon. Full costing was chosen because it provides a complete picture of production costs, including overhead costs that are often ignored by MSME entrepreneurs. This service was carried out using a qualitative method through direct interviews with MSME entrepreneurs to identify costs and to determine production costs. The results of this service with the application of full costing show that the total production cost in a period of 1 month is Rp. 11,700,000 with a Cost of Goods Manufactured (COGS) per portion of Rp. 7,446.67 and produces a profit percentage of 243.03%. In conclusion, this service can make a real contribution in improving the management skills of small and medium enterprises in the culinary field, especially by optimizing the calculation of production costs with the full costing method for geprek chicken